1250: Jean de Joinville Listens to the Story of a Renegade in Egypt (Transmediterranean History, 2022)
Using the example of an anecdote from Jean de Joinville's Histoire de Saint Louis, the article deals with Christians who embraced Islam in the context of the crusades. It provides a contemporary and modern definition of the term "renegade" and shows that Christians in the crusader milieu converted to Islam under very different circumstances. With regard to conversions, this milieu exhibited certain characteristics that were not present in the same way in other regions of intensive Christian–Muslim interaction between the eleventh and the fifteenth centuries.
Keywords: Louis IX; crusades; Egypt; Damietta; captivity; renegade; conversion to Islam